Prolonged grief disorder in refugees from Syria: qualitative analysis of culturally relevant symptoms and implications for ICD-11 - Killikelly, Clare (Mental health, religion & culture, 2021)
Prolonged Grief Disorder (PGD) is a new mental disorder recognised by the ICD-11. However, the cultural norms for grief in refugees or humanitarian migrants from Syria have not yet been established. Here we conduct an exploratory qualitative study of 10 key informant interviews with refugees from Syria with two main aims: (1) to identify common symptoms of normal or abnormal grief in refugees from Syria (2) to identify barriers to the acceptability of the new prolonged grief disorder. Three levels of qualitative analysis informed a new model of grief in Syrian refugees. Important culturally relevant symptoms such as "emotional outburst" and "weariness" emerged. The theme of "refugee experience" including sub-themes such as loss of homeland, lack of social network and ambiguous loss, emerged as potential predictors of grief severity. Finally, the level of culture and society revealed key barriers to the acceptability of the PGD diagnosis including stigma.